Progressive insulin-derived amyloidosis in a patient with type 2 diabetes. Issue 1 (1st January 2016) - Shiba, Masato; Kitazawa, Takeshi
Abstract: Here, we report a case of insulin-derived amyloidosis in the lower abdomen. The mass continued to develop even after the patient ceased injecting insulin into the mass. Histological examination led to a diagnosis of insulin-derived amyloidosis. Excision is preferable in cases of insulin-derived amyloidosis if patient's condition permits.